Transplanting Livers in Young Children - Looking Back at 100 Cases - Reya Rachel Abraham; M. M. Zameer; C. Vinay; Sanjay Rao; Ashley D'Cruz (Wolters Kluwer Medknow Publications, 2024)
Introduction: Despite advances in medical therapy, liver replacement continues to be the only definitive mode of therapy for children with end-stage liver disease (ESLD). However, its acceptance in India has been discouraging more due to financial and logistic reasons than the availability of expertise. This report outlines our journey and highlights issues pertinent to circumstances in an emerging economy like India. Aim: The aim is to review a single center's 100 case experience with liver transplantation (LT). Materials and Methods: A prospective analysis of all children who underwent LT since 2005 at our institute was done. The data were collated from a maintained structured database. Results: Hundred children underwent LT. Sixty-four were boys. Age ranged from 5 to 144 months, with a median of 17 months. The mean weight of the cohort was 7.5 kg (ranging from 3.7 to 31.5 kg), with 60% of our children weighing between 5 and 10 kg. Biliary atresia is the most common indication (57%); others include metabolic disorders, progressive familial intrahepatic cholestasis, and hepatoblastoma. Two patients were for acute liver failure. Ninety-one children underwent live donor LT (mothers being the majority of the donors). None of the donors had any major postoperative complications. Major intraoperative complications include sepsis (39%), vascular complications (17%), biliary leak (11%), and intestinal complications (11%). Early postoperative deaths occurred in 18% of patients with sepsis being most common cause. The mean follow-up was 8.5 years and the overall survival is 70%. The mean survival is time (months) = 176.1. All surviving patients were followed up and had achieved good catch up growth by 3rd and 5th years posttransplant. The long-term sequalae include recurrent intercurrent infections, graft rejection (9%), posttransplant lymphoproliferative disease (5%), and portal vein stenosis (5%). Conclusion: Our experience demonstrates the feasibility of LT in children with ESLD in India. With longer-living grafts, patients often struggle with other issues such as compliance with follow-up, financial issues, recurrent infections, and neurological problems. Close monitoring with regular follow-up of patients helps in early recognition and treatment of late-onset complications, thus helping the overall long-term outcomes.